Population structure and biofilm formation of Pseudomonas aeruginosa isolated from patients with severe burn wounds at Tygerberg Hospital - Van Biljon, Bernardus Daniel (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017